Przesłanie Tory w perspektywie synchronicznej - Stanek, Teresa (Śląskie Studia Historyczno-Teologiczne, 2007)
In view of a synchronic analysis the Torah appears as a coherent and complete work, organized around its own message – the relationship between God and man, expressed as the Covenant. The composition involves two levels: 1) the concentric arch (the events on har Sinai; the road to Si ai and from Sinai; making the covenant in Gen and Deuteronomy) that underlines the multifaceted understanding of the Covenant as a gift and an obligation; 2) the narration (the story from the beginning of the world to the death of Moses) that allows to present human history as a place of epiphany of God. As a consequence the Torah introduced faith as a basic attitude towards God, an outstanding feature of the religion of Israel.